Giving a Body a Different Face—How Men and Women Evaluate Their Own Body vs. That of Others - Voges, Mona M.; Quittkat, Hannah L.; Schöne, Benjamin; Vocks, Silja (Frontiers in Psychology, 2022)
Eating disorders affect women more than men. Women reportedly dislike their body shape more, and appreciate it less, than do men. One factor influencing body image might be the application of different standards for oneself than for other people when evaluating bodies. To investigate this possibility, we determined whether the application of double standards is different between men and women. We presented 57 women and 54 men (aged 18-30 and of average weight) with pictures of their own bodies and with pictures of average weight, overweight, and “ideal” bodies, once attached to the participants’ own face and once to another person’s face. Participants were instructed to evaluate their emotional reaction to the pictures and then to rate the various pictures on aspects of attractiveness, body fat and muscle mass. The degree of the double standard was defined as the difference between ratings of what appeared to be one’s own body and what appeared to be someone else’s according to the presented face. The analyses revealed, firstly, that both genders applied self-deprecating double standards when viewing overweight and average-weight bodies. Women, but not men, also showed self-deprecating double standards when viewing the ideal body and their own body. By contrast, men applied less double standards when viewing the ideal body and self-enhancing double standards when viewing their own body. The study suggests that young, average-weight men are more or less satisfied with their own bodies whereas young, average-weight women tend to apply a stricter standard for themselves than for others, thus devaluing their own bodies. This vulnerability to body image is hypothesized as contributing to the prevalence of eating disorders in women.